Are dyslexic children involved in delinquency? Issues and recommendations for a more fulfilling life - Athirah, Azhar; Dolly, Paul Carlo; Zamri, Hassan (SAGE Publications, 2022)
No dyslexic children are left behind; it takes a village to raise a child. Thus, fostering the achievement potential of dyslexic children and avoiding their engagement in delinquent conduct is none other than everyone’s responsibility. This research aimed to achieve a deeper understanding of the causes of delinquent behaviour in children with dyslexia and to provide solutions that would steer their attitudes and behaviour towards a more ethical and meaningful life. This qualitative study examined three samples representing dyslexic learning centres located in various places. The data were collected through online semi-structured interviews. Following that, the data were analysed utilising thematic analysis. It was discovered children with dyslexia face a variety of challenges. The community’s and parents’ stigma towards these children, such as being slow and lazy, were proven to have influenced them with deviant behaviour. It was recommended that children with learning difficulties get early detection and intervention, have a robust support system and adopt various pedagogical methods to ensure that all students could learn and guarantee dyslexics’ future success. In conclusion, early detection will enable children to get the proper intervention, preventing them from engaging in delinquent behaviours and assisting them in living in a more fulfilling life.